IMPLIKASI KESEJAHTERAAN DAN PERILAKU KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU (STUDI PADA 4 SMP NEGERI DI KOTA KENDARI PROVINSI SULAWESI TENGGARA) - Nuriadin Nuriadin (Jurnal Riset Bisnis Indonesia, 2014)
Education is one kinds of human modal investation which determines the qualityof human resourcesin a nation. The current problems which are faced by teachers is the remarkable duty and responsbilityas the demand of their profession,but in the other hand they also face the inadequacy of what theycan get from their profession. Whereas, it is highly required for teachers to increase the quality ofstudsents and create good students.The objective of this study is to find out the impact of the wellbeing,leadeship behavior moderated by organizational culture and organizational commitment towardteacher performance in 4 state Junior High Schools in kendari. The population was 380 teachers andthe samplewas 79 respondents which used proposive random sampling technique. The analysis usedstructural equation modeling wich alternative method of Partial Least Square (PLS)The result showedas follows: (1). There was a significant positive impact of well-being toward techer performance. (2).There was unsignificant positive impact of well-being toward organizational commitment. (3) Therewas unsignificant positive impact of leadership behavior toward organizational commitme. (4) Therewas a significant positive impact of leadership behavior moderated by organizational culture towrdorganizational commiment. (5) There was a signifikan positive impact of leadership behavior towardperformance. (6) There was a singnificant positive impact of organizational commitment towardteacher performance.Keywords: Well-being, Leadership Behavior moderated by Organizational Culture, OrganizationalCommitment, and Teacher Performance.